Pemberdayaan Masyarakat Pesisir Perbatasan dalam Rangka Peningkatan Kesejahteraan Masyarakat - Andri Irawan; Laurensia Tanzil (SOCIETAS, 2020)
Basically there have been many poverty assistance programs given to coastal communities, but in reality they have not succeeded in removing them from the poverty line. Lack of community involvement in each program is considered as one of the causes of the failure of programs provided by the government. The purpose of this research is to describe and analyze the border coastal community empowerment program and the factors that influence it. This type of research is descriptive with a qualitative approach. The results showed that three indicators were used as a measurement tool in analyzing the empowerment of border coastal communities, namely the indicators of the stage of awareness and the formation of behavior that had been carried out well through socialization. But what is unfortunate is that the assistance is still not routinely done. The second indicator of the ability transformation stage is carried out by providing training related to fish processing techniques, financial management and marketing. While the third indicator of the stage of increasing intellectual capacity is evidenced by the increase in the establishment of new businesses in the village community related to fishery activities and there is an increase of about 43% in the community that has expanded its business both for fishing and fish processing activities. The inhibiting factors in the implementation of the community empowerment program in Tomer Village are the low quality of human resources, the lack of assistance from the government, and related to the budget. While the supporting factors are the socio-cultural system of the local community, abundant natural resources, and the active role of the local community.